Digital Dividends: Redefining Banking Choices of Women in Bangladesh (Global Journal of Management and Business Research, 2024)
Different perceptions shape different banking choices This study investigates women s perceptions of banking channels in Bangladesh It also explores the diverse catalysts influencing banking choices and women s challenges in shaping their preferences We used a qualitative interview method to understand female perceptions of banking channels We did a thematic analysis of interviews with thirty female banking system users as the sample Using the purposive sampling method we selected the respondents for the interviews To analyze the coded interviews we employed an atlas ti 2023 a qualitative data analysis software The study found that quick and convenient access efficient financial management cost-effectiveness and high security play a significant role in shaping women s banking behaviours The study also found that women encounter challenges related to digital literacy security and complex banking systems Moreover the study found that the benefits of time-saving mechanisms are replaced by the burden of high transaction costs challenging low-income thresholds
Keywords: sustainability; women; bangladesh; financial inclusion; digital banking